Productive potentialities of the Agribusiness sector in the Apurimac region, Peru: opportunities for international trade - Reyes-Olivo, Martiniano; Méndez Soto, Rony (Seven Editora, 2023)
The region under study has, for centuries, had agriculture as its main economic activity. Since pre- Hispanic times its fertile lands have had an agricultural vocation. In the last 20 years this reality changed and migrated to gold, silver and copper mining activities mainly. Although, the macroeconomic numbers of GDP and export values are important, this has not translated into local endogenous development and produces little added value. On the other hand, the size of the region’s agricultural activity was gradually reduced. The objective of this research was to understand and identify the productive potential of the Agribusiness sector in the Apurimac region, in order to assess its opportunities for insertion into the dynamics of international trade, leveraging its comparative advantages in natural resources and its Andean agricultural supply. A qualitative approach was used with a document-type methodology based on primary and secondary information sources, which allowed the collection and classification of information with a longitudinal temporality between 2017 and 2019 with a non- experimental design level. Strengths and opportunities were found to face a process of Agribusiness export with solid bases, for which it is necessary to overcome challenges such as; the production of self-consumption, the atomization of the producers, to promote the associativity, besides strengthening the chains of value of Agro export that manage to integrate the Andean production to the large production, marketing and logistic centers of the coast and Peruvian north that allow to face successfully a process of internationalization DOI: https://doi.org/10.56238/devopinterscie-147